How We Read Oncologic FDG PET/CT. Issue 1 (December 2016) - Hofman, Michael; Hicks, Rodney
Abstract 18 F-fluorodeoxyglucose (FDG) PET/CT is a pivotal imaging modality for cancer imaging, assisting diagnosis, staging of patients with newly diagnosed malignancy, restaging following therapy and surveillance. Interpretation requires integration of the metabolic and anatomic findings provided by the PET and CT components which transcend the knowledge base isolated in the worlds of nuclear medicine and radiology, respectively. In the manuscript we detail our approach to reviewing and reporting a PET/CT study using the most commonly used radiotracer, FDG. This encompasses how we display, threshold intensity of images and sequence our review, which are essential for accurate interpretation. For interpretation, it is important to be aware of benign variants that demonstrate high glycolytic activity, and pathologic lesions which may not be FDG-avid, and understand the physiologic and biochemical basis of these findings. Whilst FDG PET/CT performs well in the conventional imaging paradigm of identifying, counting and measuring tumour extent, a key paradigm change is its ability to non-invasively measure glycolytic metabolism. Integrating this "metabolic signature" into interpretation enables improved accuracy and characterisation of disease providing important prognostic information that may confer a high management impact and enable better personalised patient care.